2018
DOI: 10.12659/msm.913290
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Induces Apoptosis in Murine Prostate Cancer Cells via Hypoxia-Inducible Factor 1-alpha (HIF-1α)/Reactive Oxygen Species (ROS)/P53 Signaling

Abstract: BackgroundResveratrol, a polyphenol found on the surface of red fruits, is able to suppress many kinds of malignancies. Nevertheless, its mechanism of action is not yet clear. Consequently, this study aimed to elucidate its influence and explore the etiology of PCCs (prostate cancer cells).Material/MethodsThe proliferation of prostate cancer cells was determined by CCK-8 assay. Cell apoptosis was determined by Hoechst staining FC assay. Cell migration was detected by scratch test. The levels of apoptosis-relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 29 publications
(29 reference statements)
1
20
0
Order By: Relevance
“…Bcl2 is an important antiapoptotic protein in cells [19]. A large number of studies [20, 21] have shown that Bcl2 expression is significantly reduced while Bax and Caspase-3, the important proapoptotic factors [22], are increased during apoptosis. In this study, we found that crocin rescued the apoptosis of hippocampal CA1 cells and prefrontal cortical neurons of AD rats, demonstrated by decreased number of apoptosis cells, decreased Bcl-2 expression, and increased Bax and Caspase-3 expression when compared with AD rats.…”
Section: Discussionmentioning
confidence: 99%
“…Bcl2 is an important antiapoptotic protein in cells [19]. A large number of studies [20, 21] have shown that Bcl2 expression is significantly reduced while Bax and Caspase-3, the important proapoptotic factors [22], are increased during apoptosis. In this study, we found that crocin rescued the apoptosis of hippocampal CA1 cells and prefrontal cortical neurons of AD rats, demonstrated by decreased number of apoptosis cells, decreased Bcl-2 expression, and increased Bax and Caspase-3 expression when compared with AD rats.…”
Section: Discussionmentioning
confidence: 99%
“…RE interferes with AKT activity and triggers apoptosis [143]. RE enhances p53 acetylation and apoptosis [144]. RE causes G1 arrest [145].…”
Section: Resveratrol (Re)mentioning
confidence: 99%
“…This article provides an overview of recent findings about the anti-PCa activity of different natural compounds (Figure 2, Table 1). [47][48][49][50][51][52][53][54]80,100,107,123,124,[135][136][137][138][139]161,163,164,186,190,191,212] The use of phytochemicals for PCa management offers several advantages. Firstly, natural products are safe and well tolerated, as well as usually economically affordable.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, while apigenin, luteolin, genistein, and celastrol inhibited the proteasomal activity and caused ubiquitinated protein accumulation in different PCa cell lines [154][155][156], quercetin, curcumin, silibinin, and tannic acid induced endoplasmic reticulum (ER) stress [157][158][159][160], a condition where unfolded/misfolded proteins accumulate in the ER lumen and promote the activation of distinct pro-death cascades, including the double-stranded RNA-dependent protein kinase PKR-like ER kinase (PERK)/eukaryotic initiation factor 2α (eIF2α)/activating transcription factor 4 (ATF4)/C/EBP homologous protein (CHOP) pathway and the inositol-requiring enzyme 1α (IRE1)/c-Jun N-terminal kinase (JNK)/p38 MAPK cascade [161]. Notably, curcumin-and silibinin-mediated ER stress was associated with generation of reactive oxygen species (ROS) and redox homeostasis alteration [159,162], which were also observed in resveratrol-and sulforaphane-treated PCa cells [163][164][165][166].…”
Section: Natural Compounds Inducing Canonical and Non-canonical Cell mentioning
confidence: 99%